Penerapan Metode Modeling The Way pada Mata Pelajaran PAI Materi Shalat Berjamaah - Derita, Derita; Ningsih, Ayu Putri (COGNITIVISM: Journal of Educational Research and Development, 2025)
This research aims to thoroughly examine the application of the Modeling the Way method in PAI (Islamic Religious Education) learning on the topic of congregational prayer in the VII grade at SMPN 35 Sijunjung. This study employs a descriptive qualitative approach. The research design takes the form of field research conducted directly at SMPN 35 Sijunjung. Data collection techniques are carried out through observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results show that this method is effective in helping students understand the procedures for congregational prayer through direct demonstration, making it easier for students to grasp both the theory and the practice. In conclusion, Modeling the Way is an appropriate method to enhance students' understanding of practical worship material such as congregational prayer.